IMPLEMENTASI ALGORITMA KRIPTOGRAFI VIGENERE CIPHER PADA PENGAMANAN PESAN TEXT BERBASIS WEB - Muhammad Rivaldi; Imam Zarkasih Harahap; Hary Isdianto; Raissa Amanda Putri (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2023)
The development of technology and information makes it easier for humans to exchange information that is not limited to distance and time. Advances in technology make it easy for people to get information instantly even though they are separated by great distances. However, this convenience is also accompanied by threats to irresponsible elements. who can access the contents of the information. Security of an information message is very necessary so that the message only reaches the intended person and other people who are not entitled to the contents of the information cannot access it. This research aims to create a text message security system using an algorithm Vigenere Cipher cryptography which aims to make the contents of the message only understandable by the recipient of the message which can increase confidentiality in exchanging information. The test results of this system can encrypt messages into ciphertext and perform decryption so that the message returns to the original message. yes